SDN hypervisor oriented vSDN controller placement algorithm - Xiaodong DONG; Zhiqiang GUO; Sheng CHEN; Xiaobo ZHOU; Heng QI; Keqiu LI (Dianxin kexue)
With the development of the future internet technology,the future network architecture which utilizes network virtualization as a tool to solve the rigidity of traditional network becomes the main stream.As a new network architecture,software defined networking provides an effective network virtualization solution.Firstly,related technology of network virtualization in SDN was concluded,distinguished differences between deploying virtual network in SDN and traditional network was compared,and aiming at the virtual network mapping problem in SDN virtualization platform,a latency sensitive SDN virtualization controller placement algorithm.At last,experiment results show that the algorithm not only can assure the delay between SDN controllers and switches in an acceptable range,but also improve the utilization efficiency of network resources.